Adjuvants Enhance the Induction of Germinal Center and Antibody Secreting Cells in Spleen and Their Persistence in Bone Marrow of Neonatal Mice - Aradottir Pind, Audur Anna; Dubik, Magdalena; Thorsdottir, Sigrun; Meinke, Andreas; Harandi, Ali M.; Holmgren, Jan; Del Giudice, Giuseppe; Jonsdottir, Ingileif; Bjarnarson, Stefania P. (Frontiers in Immunology, 2019)
Immaturity of the immune system contributes to poor vaccine responses in early life. Germinal center (GC) activation is limited due to poorly developed follicular dendritic cells (FDC), causing generation of few antibody-secreting cells (ASCs) with limited survival and transient antibody responses. Herein, we compared the potential of five adjuvants, namely LT-K63, mmCT, MF59, IC31 and alum to overcome limitations of the neonatal immune system and to enhance and prolong responses of neonatal mice to a pneumococcal conjugate vaccine Pnc1-TT. The adjuvants LT-K63, mmCT, MF59 and IC31 significantly enhanced GC formation and FDC maturation in neonatal mice when co-administered with Pnc1-TT. This enhanced GC induction correlated with significantly enhanced vaccine-specific ASCs by LT-K63, mmCT and MF59 in spleen 14 days after immunization. Furthermore, mmCT, MF59 and IC31 prolonged the induction of vaccine-specific ASCs in spleen and increased their persistence in bone marrow up to 9 weeks after immunization, as previously shown for LT-K63. Accordingly, serum Abs persisted above protective levels against pneumococcal bacteremia and pneumonia. In contrast, alum only enhanced the primary induction of vaccine-specific IgG Abs, which was transient. Our comparative study demonstrated that, in contrast to alum, LT-K63, mmCT, MF59 and IC31 can overcome limitations of the neonatal immune system and enhance both induction and persistence of protective immune response when administered with Pnc1-TT. These adjuvants are promising candidates for early life vaccination.